1983
DOI: 10.1210/endo-113-5-1910
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages: A Source of Luteotropic Cybernins

Abstract: A macrophage homogenate contained substances which stimulated primary cultures of mouse granulosa cells to secrete more progesterone. The response to the luteotropic substances was similar to that observed when intact macrophages were co-cultured with granulosa cells. The bioactive polypeptides present in cytosolic and particulate fractions of cell homogenates were non-dialyzable, heat labile and trypsin sensitive. When the surface of intact macrophages was treated with trypsin there was a loss of activity fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

1985
1985
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(19 citation statements)
references
References 0 publications
1
18
0
Order By: Relevance
“…These results are in agreement with previous studies demonstrating the presence of macrophages in the mouse ovary [18], rat ovary [31], and human ovary [32]. Our morphological observations of an intimate relationship of macrophages to luteal cells support the demonstrated capability of macrophages to stimulate progesterone production in the murine corpus luteum [33,34] and human granulosa-luteal cells [35]. Together, this evidence invokes a cooperative role of monocyte-macrophages in luteal tissue function.…”
Section: Discussionsupporting
confidence: 92%
“…These results are in agreement with previous studies demonstrating the presence of macrophages in the mouse ovary [18], rat ovary [31], and human ovary [32]. Our morphological observations of an intimate relationship of macrophages to luteal cells support the demonstrated capability of macrophages to stimulate progesterone production in the murine corpus luteum [33,34] and human granulosa-luteal cells [35]. Together, this evidence invokes a cooperative role of monocyte-macrophages in luteal tissue function.…”
Section: Discussionsupporting
confidence: 92%
“…These observations lead to the speculation that the ovarian macrophages contribute to the luteolysis and atresia of follicles through their phagocytic activity. Alternatively, it has been demonstrated in the rat that the co-cultivation of ovarian macrophages with luteal cells leads to enhanced progesterone secretion from the luteal cells in vitro, indicating a paracrine function of ovarian macrophages (KIRSCH et al, 1983). It is also well known that luteal cells undergo hypertrophy with the augmented secretion of progesterone during pregnancy, However, we demonstrated that the macrophages in the corpora lutea were few in number and their cell size diminished during pregnancy.…”
Section: Discussionmentioning
confidence: 41%
“…It is known that macrophages migrate into the ruptured follicle after ovulation and reside in newly formed luteal tissue [27,49]. It is inferred that these macrophages play a role in regulating luteal function by secreting cytokines [28,30,35,36,[50][51][52][53][54][55][56]. We found that the effect of PRL on progestin synthesis by rat luteal tissue was profoundly altered by removal of the spleen, a major source of peripheral macrophages [52], but, the effects of the splenectomy were virtually nullified by implanting splenocytes or splenic macrophages [51][52][53][54].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, it is reported that large luteal cells and small luteal cells in rat corpus luteum were stained with the anti-TGF/31 and anti-TGF/32, respectively [24]. TGF/3 is one of the cytokines secreted from macrophages [2,33], and macrophages are known to be present in corpora lutea [25][26][27][28][29][30][31][32]. The luteal macrophage is therefore also a possible candidate for the anti-TGF/3 positive cell in the corpus luteum.…”
Section: Transformingmentioning
confidence: 99%